Pengaruh Motivasi Intrinsik dan Ekstrinsik Terhadap Minat Mahasiswa Dalam Memilih Konsentrasi Akuntansi Syariah yang Dimoderasi Prestasi Akademik - Junior, M. Fadil; Ramadhan, Abid; Riyanti (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2025)
This study aims to analyze the influence of intrinsic and extrinsic motivation on students’ interest in choosing the Sharia Accounting concentration, with academic achievement as a moderating variable. The research method used is a quantitative approach with a purposive sampling technique, involving 61 3rd semester students of the Accounting Study Program, Universitas Muhammadiyah Palopo. Data were collected through questionnaires and analyzed using multiple linear regression with the help of SPSS 25 software. The results of the study indicate that both intrinsic and extrinsic motivation have a positive influence on students’ interest in choosing the Sharia Accounting concentration. However, extrinsic motivation has a more dominant influence than intrinsic motivation. Academic achievement as a moderating variable does not show a significant influence in strengthening the relationship between motivation and student interest. This finding indicates that external factors, such as career opportunities and financial incentives, play a greater role in attracting student interest than internal factors such as learning satisfaction or the desire to develop. The implication of this study is the need for educational institutions to pay more attention to external factors in increasing student interest in Sharia Accounting, such as providing information on career prospects and incentives in the field. In addition, the development of learning strategies that can increase students’ intrinsic motivation is also an important factor that needs to be considered.